Eosinophil Count Is a Common Factor for Complex Metabolic and Pulmonary Traits and Diseases: The LifeLines Cohort Study - Amini, Marzyeh; Bashirova, Dinara; Prins, Bram P.; Corpeleijn, Eva; Bruinenberg, Marcel; Franke, Lude; Harst, Pim van der; Navis, Gerjan; Wolffenbuttel, Bruce H. R.; Stolk, Ronald P.; Wijmenga, Cisca; Postma, Dirkje S.; et al. (PloS one, 2016)
There is ongoing debate on the association between eosinophil count and diseases, as previous studies were inconsistent. We studied the relationship of eosinophil count with 22 complex metabolic, cardiac, and pulmonary traits and diseases. From the population-based LifeLines Cohort Study (N = 167,729), 13,301 individuals were included. We focused on relationship of eosinophil count with three classes of metabolic (7 traits, 2 diseases), cardiac (6 traits, 2 diseases), and pulmonary (2 traits, 2 diseases) outcomes. Regression analyses were applied in overall, women and men, while adjusted for age, sex, BMI and smoking. A p-value of <0.00076 was considered statistically significant. 58.2% of population were women (mean±SD 51.3±11.1 years old). In overall, one-SD higher of ln-eosinophil count was associated with a 0.04 (±SE ±0.002;p = 6.0×10-6) SD higher levels in ln-BMI, 0.06 (±0.007;p = 3.1×10-12) SD in ln-TG, 0.04 (±0.003;p = 7.0×10-6) SD in TC, 0.04 (±0.004;p = 6.3×10-7) SD in LDL, 0.04 (±0.006;p = 6.0×10-6) SD in HbA1c; and with a 0.05 (±0.004;p = 1.7×10-8) SD lower levels in HDL, 0.05 (±0.007;p = 3.4×10-23) SD in FEV1, and 0.09 (±0.001;p = 6.6×10-28) SD in FEV1/FVC. A higher ln-eosinophil count was associated with 1.18 (95%CI 1.09-1.28;p = 2.0×10-5) odds ratio of obesity, 1.29 (1.19-1.39;p = 1.1×10-10) of metabolic syndrome, 1.40 (1.25-1.56;p = 2.7×10-9) of COPD and 1.81 (1.61-2.03;p = 1.0×10-23) of asthma. Similar results were found in women. We found no association between ln-eosinophil count either with blood pressure indices in overall, women and men; or with BMI, LDL, HbA1c and obesity in men. In a large population based cohort, we confirmed eosinophil count as a potential factor implicated in metabolic and pulmonary outcomes.